(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In this article, the role of chemistry in the field of aviation is covered by chemical processes, especially chemical processes to ensure the effectiveness and security of flights. Aviation fuels will analyze the types of air fuel, their ingering features, the chemical reactions that occur in the conditions conditions, and new chemical technologies used in the atmosphere. Modern chemical solutions to reduce environmental security and fuel to the environment will also be considered.